2009
DOI: 10.1021/jp901267k
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Production of Aligned Long Boron Nitride Nanofibers by Multijet/Multicollector Electrospinning

Abstract: Boron nitride nanofibers (BNNFs) with alignment and large length have been prepared on a large scale by electrospinning the precursor fibers and subsequent nitridation. A multijet/multicollector electrospinning system is constructed by simply arranging three jets and three tip collectors abreast. By this system the aligned precursor fibers with lengths over 13 cm are collected throughout a very large length of 68 cm. The alignment of the electrospun precursor fibers is mainly induced by the converging electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 51 publications
(100 reference statements)
0
44
0
Order By: Relevance
“…Another modification by additional electrodes in multi-jet process was an auxiliary electrode. Placed in parallel to the collector, either supporting the nozzles [15,22], or working as additional collector [23], the auxiliary electrode controls the electric field uniformity in the multi-jet electrospinning process. Tomaszewski and Szadkowski, and Yang et al suggested that appropriate nozzles distribution in multi-jet electrospinning system facilitates collecting process of nanofibers [24,25].…”
Section: E V E N T H O U G H T H E I N D U S T R I a L A P P L I C A mentioning
confidence: 99%
“…Another modification by additional electrodes in multi-jet process was an auxiliary electrode. Placed in parallel to the collector, either supporting the nozzles [15,22], or working as additional collector [23], the auxiliary electrode controls the electric field uniformity in the multi-jet electrospinning process. Tomaszewski and Szadkowski, and Yang et al suggested that appropriate nozzles distribution in multi-jet electrospinning system facilitates collecting process of nanofibers [24,25].…”
Section: E V E N T H O U G H T H E I N D U S T R I a L A P P L I C A mentioning
confidence: 99%
“…Electrospinning technique can also be used for fabricating nanofibers composed by non-oxide ceramics including carbide, boride, nitride, silicide and sulphide [38,50,[79][80][81][82][83][84][85][86][87]. Wu et al synthesized nitride nanofibers via electrospinning for the first time [50].…”
Section: Electrospinning Of Ceramic Nanofibersmentioning
confidence: 99%
“…Such promising materials include mesoporous silica, mesoporous carbon, nanocarbon, and nanofiber [6][7][8][10][11][12][13][14]. Increases in surface area and surface functionalization of adsorbents with desired functional groups can increase the adsorption rate of heavy metals [15][16][17][18][19][20]. Due to their high adsorption capacity , nanoporous nanofibers are considered to be efficient adsorbents for removing heavy metals and organic pollutants from water [6,7,11,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%